The Sensitive Woman in the Story Collection ‘Grihpravesh’ : ‘गृहप्रवेश’ कहानी संग्रह की संवेदनशील नारी - Yadav, Ramavatar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Suryabala’s stories deeply explore the inner anguish of women, familial relationships, and the changing social environment. In the story ‘Grihpravesh’, the affectionate bond between a brother and sister is woven together with threads of memory and emotion. ‘Bauji Aur Bandar’ reflects the self-centeredness of the modern woman, where family values seem to be fading. ‘Salamat Jageerein’ portrays a mother’s affection and the gradual emotional detachment that comes with time. Meanwhile, ‘Geeta Chaudhary Ka Aakhri Sawaal’ reveals the struggling condition of a talented girl who is gradually losing her abilities under the weight of domestic responsibilities. Without resorting to slogans or dramatic declarations, Suryabala presents the pain, sensitivity, and emotional states of women in a very natural yet deeply touching manner. Her stories highlight the contradictions in women’s lives and compel readers to reflect on an emotional level. This collection offers a new perspective to the discourse on women. Abstract in Hindi Language: सूर्यबाला की कहानियाँ स्त्री की अंतःवेदना, पारिवारिक संबंधों और बदलते सामाजिक परिवेश की गहन पड़ताल करती हैं। ‘गृहप्रवेश’ कहानी में भाई-बहन के स्नेहिल रिश्ते को स्मृति और संवेदना के ताने-बाने से बुना गया है। ‘बाऊजी और बंदर’ आधुनिक नारी की आत्मकेंद्रितता को दर्शाती है, जहाँ पारिवारिक मूल्य पीछे छूटते नजर आते हैं। ‘सलामत जागीरें’ में माँ की ममता और समय के साथ कम होती भावनात्मकता को चित्रित किया गया है। वहीं ‘गीता चैधरी का आखिरी सवाल’ में एक होनहार लड़की की संघर्षपूर्ण स्थिति को उजागर किया गया है, जो घरेलू जिम्मेदारियों में अपनी प्रतिभा खोती जा रही है। सूर्यबाला ने बिना नारेबाजी किए स्त्री की पीड़ा, संवेदना और मनोभावों को बहुत ही सहज, परंतु मार्मिक रूप से प्रस्तुत किया है। उनकी कहानियाँ नारी जीवन की विसंगतियों को उभारती हैं और पाठकों को संवेदना की धरातल पर सोचने को विवश करती हैं। यह संग्रह नारी विमर्श को एक नई दृष्टि प्रदान करता है। Keywords: नारी संवेदना, परिवार, आत्मसंघर्ष, सूर्यबाला, कथा-साहित्य